Text Data Security Using Stream Cipher Algorithm - S Supiyanto; Agung Dwi Saputro; Muhammad Asghar (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2023)
The Stream Cipher cryptographic algorithm is a cryptographic algorithm that can be used to secure symmetric key-type data. The Stream Cipher algorithm uses the same key when performing encryption and decryption. In carrying out the encryption process, the Stream Cipher algorithm uses the stream cipher method, where the cipher comes from the result of an XOR operation between the plaintext bit and the key bit. This study aims to implement the Stream Cipher algorithm with a Matlab programming language for text security. The text data used in this study is in the form of a file with a txt extension. The stages of research methods included literature studies, algorithm analysis, program design, and testing. The method used in this study is to apply the Stream Cipher algorithm to a programming language to produce an application that can be used for data security. The output of this research is the creation of an application program that can be used to secure text data so that the information contained is not easily stolen or misused by irresponsible people. The test results in the study using a key that was modulo-kan 65 first will produce a random message in the form of clear characters while using a key that is not modulated will produce a random message that is less clear in the form of boxes.